Hear together - Lim, Gladys Cheng Hui (Nanyang Technological University, 2020)
This paper presents Hear Together, a pilot communication campaign on age-related hearing loss by four final-year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University, Singapore. Hearing loss is an issue that affects over half of the population aged above 60 in Singapore. Based on our research findings, social influence is a factor that affects elderly intention to screen. As such, Hear Together targets informal caregivers aged 21 to 59, such as family and friends to help influence those aged above 60 to attend a hearing screening. Hear Together sought to address informal caregivers’ knowledge gaps regarding age-related hearing loss, while improving their attitudes and perceived norms towards hearing screenings. Campaign tactics such as a web comic series, screening testimonials, expert videos and a Facebook livestream were created to achieve these objectives. 10 pop-up booths were held in Bedok to encourage sign-ups for hearing screenings. The campaign, conducted between January and March 2020 managed to get 109 elderly to attend a hearing screening, of which 52 were influenced by their caregivers. Hear Together also improved knowledge levels by 9.8%, attitudes by 3.3% and perceived norms by 3.4%. Based on the learnings from the campaign, a recommendation for future similar initiatives is to investigate the influence of convenience and cost in influencing hearing screening uptake in the elderly. Campaign sustainability initiatives with partners such as Changi General Hospital and The Singapore Association for the Deaf will also be discussed in this paper.